Identification and Isolation of Caffeic, Chlorogenic and Ferulic Acids in Aerial Parts of Capparis spinosa wildly grown in Iraq - Asmaa M. Hussein; Enas J. Kadum (College of Pharmacy University of Baghdad, 2020)
Capparis spinosa is one of the oldest genera grown in Iraqi land with worldwide traditional medicinal uses beside the culinary uses. These uses were own to the presence of many phytochemical including flavonoids, polyphenols. Among the reported polyphenolic acids are caffeic, chlorogenic and ferulic acids with well-known powerful antioxidant properties. The present work aimed to identify the presence of these polyphenolic acids in Iraqi caper naturally gown in the rural area of middle Iraq following standard chromatographic procedures. Aerial parts of the plant (buds, berries and leaves) were extracted with hydroalcoholic solvent by maceration method. Thin layer chromatographic techniques and HPLC analysis were performed to identify the presence of polyphenolic acids in ethyl acetate fraction of the hydroalcoholic extracts. The result obtained in this work revealed the presence of these phenolic acids in investigated extracts. Chromatographic analysis confirms the presence of considerable amounts of these acids in ethyl acetate fraction when the separated spots were compared with Rf values and UV spectra of standards. Such data give a promising use of aerial parts of Iraqi caper for globally reported medicinal uses.